Finite Element Analysis of Stress Distribution in Bar-Attachment Systems for Implant-Retained Palateless Overdentures - Mostafa Almkrhi (المجلة الأفروآسيوية للبحث العلمي, 2025)
This study investigates the stress distribution in implant bar over-denture systems for maxillary palateless over-dentures. By comparing different attachment types and bar configurations under various loading conditions, the aim is to optimize design and minimize biomechanical risks.Materials and Methods: A three-dimensional finite element model of a maxillary arch with four implants was developed. Two bar-attachment systems were evaluated: a Hader bar with clips and a milled bar with Locator attachments. The models were designed to explore the effect of different inter-implant distances and bar orientations on stress distribution. Elastic properties were assigned to the materials, and static occlusal loads (100 N) were applied vertically, obliquely, and laterally to simulate masticatory forces. Results: Stress distribution was highly influenced by the attachment type and loading direction. The Locator attachment system demonstrated a more favorable stress distribution compared to the Hader bar, which showed higher stress concentrations at the bar-attachment interfaces and the peri-implant bone. Oblique and lateral loads generated significantly higher stresses than vertical loads. A wider inter-implant distance reduced peak stress levels by promoting better load sharing between implants. Conclusion: The design of the bar-attachment system critically affects the biomechanical performance of palateless overdentures. For optimal stress distribution, clinicians should consider configurations that enhance load sharing, such as using resilient attachments like the Locator and maximizing inter-implant distance copy result.